Calcium-Dependent Arrhythmogenic Foci Created by Weakly Coupled Myocytes in the Failing Heart. Issue 12 (8th December 2017) - Lang, Di; Sato, Daisuke; Jiang, Yanyan; Ginsburg, Kenneth S.; Ripplinger, Crystal M.; Bers, Donald M.
Abstract : Rationale: : Intercellular uncoupling and Ca 2+ (Ca) mishandling can initiate triggered ventricular arrhythmias. Spontaneous Ca release activates inward current which depolarizes membrane potential (Vm ) and can trigger action potentials in isolated myocytes. However, cell-cell coupling in intact hearts limits local depolarization and may protect hearts from this arrhythmogenic mechanism. Traditional optical mapping lacks the spatial resolution to assess coupling of individual myocytes. Objective: : We investigate local intercellular coupling in Ca-induced depolarization in intact hearts, using confocal microscopy to measure local Vm and intracellular [Ca] simultaneously. Methods and Results: : We used isolated Langendorff-perfused hearts from control (CTL) and heart failure (HF) mice (HF induced by transaortic constriction). In CTL hearts, 1.4% of myocytes were poorly synchronized with neighboring cells and exhibited asynchronous (AS) Ca transients. These AS myocytes were much more frequent in HF (10.8% of myocytes, P <0.05 versus CTL). Local Ca waves depolarized Vm in HF but not CTL hearts, suggesting weaker gap junction coupling in HF-AS versus CTL-AS myocytes. Cell-cell coupling was assessed by calcein fluorescence recovery after photobleach during intracellular [Ca] recording. All regions in CTL hearts exhibited faster calcein diffusion than in HF, with HF-AS myocyte being slowest. In HF-AS, enhancing gap junction conductance (with rotigaptide) increased coupling and suppressed Vm depolarization during Ca waves. Conversely, in CTL hearts, gap junction inhibition (carbenoxolone) decreased coupling and allowed Ca wave-induced depolarizations. Synchronization of Ca wave initiation and triggered action potentials were observed in HF hearts and computational models. Conclusions: : Well-coupled CTL myocytes are effectively voltage-clamped during Ca waves, protecting the heart from triggered arrhythmias. Spontaneous Ca waves are much more common in HF myocytes and these AS myocytes are also poorly coupled, enabling local Ca-induced inward current of sufficient source strength to overcome a weakened current sink to depolarize Vm and trigger action potentials. Abstract : Supplemental Digital Content is available in the text.